Searching for Fast Radio Transients with SKA Phase 1 - Colegate, Timothy; Clarke, Nathan (CSIRO, 2011)
The Square Kilometre Array (SKA) provides an excellent opportunity for low-cost searches for fast radio transients. The increased sensitivity and field of view of the SKA compared with other radio telescopes will make it an ideal instrument to search for impulsive emission from high–energy density events. We present a high-level search ‘use case’ and propose “event rate per unit cost” as a figure of merit to compare transient survey strategies for radio telescope arrays; we use “event rate per beam formed and searched” as a first-order approximation of this measure. Key results are that incoherent (phase-insensitive) combination of antenna signals achieves the highest event rate per beam, and that 50–100 MHz processed bandwidth is sufficient for extragalactic searches with SKA Phase 1; the gain in event rate from using the full available bandwidth is small. Greater system flexibility will enable more effective searches, but need not drive the top-level system requirements beyond those already proposed for the SKA. The most appropriate search strategy depends on the observed sky direction and the source population; for SKA Phase 1, low-frequency aperture arrays tend to be more effective for extragalactic searches, and dishes more effective for directions of increased scatter broadening, such as near the Galactic plane.